Transformasi Tafsir Al-Qur’an di Era Media Digital: Analisis Metodologi Tafsir dalam Channel Youtube "Kajian Tafsir Al-Ma’rifah" - Yuningsih, Hartati; Ghany, Abdul (Al-Qudwah, 2024)
The transformation of Qur'anic exegesis methodology through digital platforms has revolutionized the way the science of tafsir is conveyed and received by the public. The limitations of accessibility and interactivity in traditional methods, which rely on oral and written explanations, have necessitated a new, more engaging, and interactive approach through digital technology. The purpose of this research is to analyze and evaluate the methodology of Qur'anic interpretation used in the tafsir studies on the YouTube channel "Kajian Tafsir Al-Ma'rifah" by Musthafa Umar. This study is descriptive qualitative research utilizing a literature review method. Primary data was collected from the tafsir study videos on the "Kajian Tafsir Al-Ma'rifah" YouTube channel, while secondary data was obtained from textbooks, scholarly articles, and relevant tafsir books. The findings of the research indicate that the use of visual and audio elements in the tafsir videos enhances understanding and information retention among the audience. Additionally, interactive features such as comments, likes, and shares create a dynamic dialogue between the interpreter and the audience, strengthening engagement and participation in the learning process. Digital technology, through platforms like YouTube, not only facilitates access to Qur'anic exegesis but also enriches its delivery methods, making it more inclusive and effective in reaching a global audience. This research contributes to the literature on the transformation of tafsir methodology in the digital era and provides practical recommendations for the development of dakwah through digital platforms.Abstrak: Transformasi metodologi penyajian tafsir Al-Qur'an melalui platform digital telah mengubah cara penyampaian dan penerimaan ilmu tafsir di kalangan masyarakat. Keterbatasan aksesibilitas dan interaktivitas dalam metode tradisional yang mengandalkan penjelasan lisan dan tulisan mendorong perlunya pendekatan baru yang lebih menarik dan interaktif melalui teknologi digital. Tujuan penelitian ini adalah untuk menganalisis dan mengevaluasi metodologi penafsiran Al-Qur'an yang digunakan dalam kajian tafsir di channel YouTube Kajian Tafsir Al-Ma'rifah oleh Musthafa Umar. Jenis penelitian ini adalah penelitian kualitatif deskriptif dengan metode studi kepustakaan. Data primer diambil dari video-video kajian tafsir di channel YouTube Kajian Tafsir Al-Ma'rifah, sedangkan data sekunder diperoleh dari buku-buku teks, artikel ilmiah, dan kitab-kitab tafsir yang relevan. Hasil penelitian menunjukkan bahwa penggunaan elemen visual dan audio dalam video tafsir meningkatkan pemahaman dan retensi informasi di kalangan audiens. Selain itu, fitur interaktif seperti komentar, like, dan share menciptakan dialog yang dinamis antara penafsir dan audiens, memperkuat keterlibatan dan partisipasi dalam proses pembelajaran. Teknologi digital melalui platform seperti YouTube, tidak hanya mempermudah akses terhadap tafsir Al-Qur'an tetapi juga memperkaya metode penyampaiannya, membuatnya lebih inklusif dan efektif dalam menjangkau audiens global. Penelitian ini berkontribusi pada literatur tentang transformasi metodologi tafsir di era digital dan memberikan rekomendasi praktis bagi pengembangan dakwah melalui platform digital.